Preserving heritage sites of Dhaka City using 3D modeling and virtual reality technology - Islam, Raisa; Ahmed, Salsabil; Himalay, Sadman Shawmik (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.